Estimación de la estatura de una persona a partir de las dimensiones de las estructuras dentales - Brito Arízaga, Joseline Elizabeth (2019)
Forensic anthropology uses various reconstructive methods to establish the identify of dead bodies through the discovery of age, ancestral pattern, size, sex, and race, which are then compared with those of missing persons seeking points of agreement, due the teeth are the hardest structures of the human body, it is more resistant to damage and deterioration, and provides information by establishing information about the individual.The objective of this research is to establish the height of a person based on the dimension of the dental structures among the students of the 3rd semester of Dentistry Major at the Universidad Nacional de Chimborazo during the period October 2018 to –March 2019, where the quantitative, transversal, descriptive and correlational research has taken of the hypothesis testing. 50 study models were collected; in which the mesio-distal measurements of the lower anterior parts of the right and left sides were determined. The data was recorded on a data collection sheet using the observation technique, applying the Carrea Method. After performing a statistical analysis, it was concluded that there is no significant difference between the actual height and the information obtained by the Carrea Method, so it is a viable formula for the determination of height in cases of identification.